An analysis of the implications of factionalism on economic development in Zimbabwe in the 21st century - Ngundu, Shantell Tatenda (Midlands State University, 2018)
Factionalism in Zimbabwe has always been an issue dating back to the pre-independence era, it has reaped many unbearable fruits in the 21st century .The struggle for power between the two main political parties ZANU-PF and MDC has seriously affected the economy. Factionalism contributed positively and negatively to the economic development of Zimbabwe. Its effects however are more negative than positive The causes of factionalism include issues to do with struggle for power ,violation of constitutions, undemocratic tendencies by leaders, dictatorial controls, tribalism and regionalism, injustice, unfair wealth, property, service and material distribution between the members ideological differences, issues to do with ethics, morals and religion .This has led to economic deterioration as political leaders spend more time fighting for power rather than coming up with economic strategic plans for a better Zimbabwe. However, factionalism has its benefits factions promote generational change looking at Zimbabwe as one nation where an entire generation has struggled roughly to formulate an important contribution to the country’ s politics. It increases debate and competition within a party which is good and can moderate a party in its actions.